Insurance Research and Medical Ethics - Lorie Terry (Pain Research and Management)
On January 1, 1995, Saskatchewan adopted a radical, no-fault system for motor vehicle accident insurance. Virtually no room was left for injured victims to sue for damages, whether for pain and suffering or for economic compensation. In fact, the no-fault system removed benefits for pain and suffering altogether. Apart from the concern that arose at the denial of justice in relation to economic matters and the blanket denial of pain, there was concern over the arrangements for medical care. Under the new Automobile Accident Insurance Act, injured persons were entitled to compensation and payment for treatment, as managed by their own doctors, chiropractors or physiotherapists for the first six weeks subsequent to an injury. Thereafter, they were required to be seen by insurance company-appointed doctors, chiropractors or physiotherapists if they wished the income replacement benefits to continue, treatment to be provided or both. They also were obliged to accept the recommendations of the insurance company doctors for the next 12 weeks, under what was called 'secondary rehabilitation'. If they claimed not to be well at the end of that period, further rehabilitation, described as 'tertiary rehabilitation' would be ordered. Two specific 'in-patient' centres were established for tertiary rehabilitation in different parts of the province (Regina and Saskatoon), and victims thought to be in need of tertiary rehabilitation had to travel if they did not live in either Regina (the provincial capital) or Saskatoon. The administration and treatment of individuals under these systems were so unacceptable to many individuals that a widespread resistance movement was generated and was established as the Coalition Against No-Fault Insurance on August 28, 1998, opening with simultaneous protests in Regina, Saskatoon, Prince Albert North Battleford and Estevan, each one organized by a local victim of the no-fault insurance scheme.